2021
DOI: 10.1007/s40615-021-01073-w
|View full text |Cite
|
Sign up to set email alerts
|

Shared Cultural Values Influence Mental Health Help-Seeking Behaviors in Asian and Latinx College Students

Abstract: The current study sought to understand the influence of cultural values on mental health attitudes and help-seeking behaviors in college students of diverse ethnic backgrounds. Asian and Latinx college students (N = 159) completed an online survey in which they reported on their adherence to cultural values as measured by ethnicity-specific cultural values and general attitudes towards mental health. Factor analysis revealed two common factors of cultural values irrespective of ethnicity: Interdependent Orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…All Approach/Encourage responses include either consulting with a mental health provider outside of one's family or referring the peer in mental distress to mental health support services provided by mental health provider outside of the family. Thus, in an extension of the extant literature (Barthelemy, 2017; Suwinyattichaiporn & Johnson, 2020; Zhou et al., 2021), our findings indicated that decreases HSI students’ barriers to seeking counseling were predictive of increases in the likelihood that they responded in supportive ways when encountering a peer in mental distress. Based on the content of the MDRS, these supportive responses might include consulting with or referring a peer in distress to someone outside of the family, for example, a college counselor.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…All Approach/Encourage responses include either consulting with a mental health provider outside of one's family or referring the peer in mental distress to mental health support services provided by mental health provider outside of the family. Thus, in an extension of the extant literature (Barthelemy, 2017; Suwinyattichaiporn & Johnson, 2020; Zhou et al., 2021), our findings indicated that decreases HSI students’ barriers to seeking counseling were predictive of increases in the likelihood that they responded in supportive ways when encountering a peer in mental distress. Based on the content of the MDRS, these supportive responses might include consulting with or referring a peer in distress to someone outside of the family, for example, a college counselor.…”
Section: Discussionsupporting
confidence: 66%
“…These findings are particularly promising considering college counselors’ need for mental health screening tools with validated scores among HSI students. Our findings suggest that the internal structure of Revised FSV Scale and the Approach/Encourage scale of the MDRS extends to HSI students, a distinct population with unique mental health needs (Barthelemy, 2017; Suwinyattichaiporn & Johnson, 2020; Zhou et al., 2021). Specifically, the results of the CFAs extend the generalizability of scores on the Revised FSV Scale and Approach/Encourage scale of the MDRS to a large sample of HSI students.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations